Cooperative Federalism and Policy Implementation: The Children’s Health Insurance Program for the Latino Population - Stevens, Mark; Sa, Yongjin (Advances in Social Sciences Research Journal, 2018)
With ongoing debates in Washington about the proper role of government in the provision of health care, especially during tight fiscal times, this paper examines current federal-state relations on the implementation of the Children’s Health Insurance Program. The paper focuses specifically on the cooperative nature of the relationship between federal and state governments with regards to insuring low-income, uninsured Latino children. While the cooperative nature will continue, program implementation will be difficult to maintain in the future because of the uncertainties of resources provided to the states, commitment of political leaders to the program’s goals, the complexity of joint action involved, and the diversity of the Latino population. The theoretical framework, program context, and findings of this research are specifically discussed.